Investigating chemical and microstructural evolution at dissimilar metal welds - Clark, John William Gordon (2015)
Dissimilar metal welds (DMWs) are widely used in steam vessels in thermal power stations to join low-temperature alloys, such as steels, to high temperature alloys, such as nickel-based alloys. This provides a cost-effective manufacturing solution. However, there is a history of DMWs failing due to creep in service environments. Many investigations have been performed on weld systems and failures in the traditional 2.25Cr-1Mo (P22) steels, but fewer have been performed on newer 9Cr-1Mo steels, such as P91 and P92. Failures involving these newer steels continue to occur, for reasons which are not thoroughly understood. The factors involved are believed to include system stresses, differences in thermal expansion and microstructural evolution due to interdiffusion across the weld interface. The overall aim of this research was to investigate the chemical and microstructural stability of a range of DMWs involving P91 and P92 steels.